Inmunidad, anafilaxia y alergia - Bianchi, Andrés E. (1943)
Before studying allergic inflammation the author tries to explain the true signification of Allergy and that is why he refers the history of Immunity, Anaphylaxis and Allergy; he finishes saying that a simple grammatical examination and their pure chronology are not enough to its explanation but on the contrary, true morphologic substractum of every state must be establish exactly and graphically and thus it is possible compare among them and to establish their resemblances and differences.